Chemotherapy Controls Metastasis Through Stimulatory Effects on GRP78 and Its Transcription Factor CREB3L1 - Raiter, Annat; Lipovetsky, Julia; Hyman, Lucila; Mugami, Shany; Ben-Zur, Tali; Yerushalmi, Rinat (Frontiers in Oncology, 2020)
To achieve a cure for metastatic breast cancer, further understanding of molecular drivers of the metastatic cascade is essential. Currently, chemotherapy regimens include doxorubicin and paclitaxel which act in part by inducing the unfolded protein response (UPR). The master regulator of the UPR, glucose regulated protein 78 (GRP78), localizes on the surface of tumor cells and is associated with metastatic disease. Cyclic AMP responsive element binding protein 3-like 1 (CREB3L1), a member of the UPR, is a breast cancer metastasis suppressor that acts on cyclic AMP to promote the expression of target genes including GRP78. The aim of the present study was to evaluate the effects of chemotherapy on CREB3LI and cell-surface GRP78 expression and its association with the development of breast cancer metastasis. For this purpose, we use breast cancer cells migration in vitro assays and an in vivo metastatic mouse model. The results showed that chemotherapy activated CREB3L1 and enhanced cell-surface GRP78 expression specifically in triple-negative breast cancer cells, reducing their migration and metastatic potential. CREB3L1 knockout (KO) in the triple negative MDAMB231cell line using CRISPR/Cas9 technology led to inhibition of GRP78 expression and abrogation of the CREB3L1 metastatic suppression function. Inoculation of CREB3L1-KO MDAMB231 cells into a mouse metastatic model induced a massive metastatic profile which chemotherapy failed to prevent. These findings elucidate a potential pathway to the development of a novel treatment strategy for metastatic TNBC based on modulating CREB3L1 and cell-surface GRP78 expression by chemotherapy and GRP78-targeted drugs.